A super hydrophobic coating and its preparation method and application
By mixing fluoropolymer with ceramic powder and atomizing and drying and thermal spraying technology, a super-hydrophobic, wear-resistant and anti-corrosion coating is formed, which solves the problem of easy wear of the existing super-hydrophobic coating and realizes the coating Long-term effectiveness and efficient anti-fouling performance.
Patent Information
- Application Number
- CN202411448315.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The existing superhydrophobic coatings are prone to wear in practical applications, resulting in poor durability and stability, limiting their wide application in various fields.
By mixing the fluoropolymer with the ceramic powder and atomizing and drying, the composite powder is deposited on the substrate by thermal spraying technology to form a coating with superhydrophobic, wear-resistant, anti-corrosion and self-cleaning functions, adjusting the ceramic powder and the content The particle size and mixing ratio of the fluoropolymer form a nanoscale transition layer to enhance the binding force of the coating.
The uniformity and wear resistance of the coating are achieved, while maintaining hydrophobic properties, which can effectively resist mechanical damage under friction conditions, and ensure the long-term effectiveness of the coating.
Smart Images

Figure CN118956211B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of coatings, and in particular to a super-hydrophobic coating and a preparation method and application thereof. Background Art
[0002] Superhydrophobic coatings have attracted extensive attention due to their excellent liquid repellency and important application value in the fields of corrosion protection, self-cleaning, oil-water separation and fluid drag reduction. Superhydrophobic surfaces not only have self-cleaning functions, but also have special functions such as corrosion resistance, anti-biological attachment, anti-icing and anti-frost. Therefore, they have broad application prospects in the fields of surface protection of marine ships and offshore platforms, outdoor equipment for power transmission and construction.
[0003] However, super-hydrophobic materials have not been widely used at present, mainly because the artificial super-hydrophobic surface is different from the super-hydrophobic surface in nature. At present, chemical methods (such as sol-gel method, electrostatic spinning method and polymer casting method, etc.) are used to prepare low surface energy organic super-hydrophobic coating or bionic micro-convex structure. There are two problems in the above preparation of super-hydrophobic coating: on the one hand, although the steps of organic hydrophobic coating preparation method are simple and easy to operate, the prepared coating has poor bonding force, is not impact-resistant, and has poor environmental adaptability, and is often faced with problems such as coating powdering, blistering, cracking and hydrophobic function decline. On the other hand, due to the fragile micro-nano structure of super-hydrophobic surface, its mechanical damage resistance, especially wear resistance, is poor. When the micro-nano size required for artificial super-hydrophobic surface is contacted, collided, bent, and particularly rubbed by foreign objects in the service environment, the damage of its own structure will cause the decline or even disappearance of super-hydrophobic characteristics.
[0004] Superhydrophobic coatings face certain challenges in practical applications, mainly due to the easy wear characteristics of their external hydrophobic surface. This characteristic affects the durability and stability of superhydrophobic coatings, thus limiting their wide application in various fields.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The object of the present invention is to provide a super-hydrophobic coating and a preparation method and application thereof.
[0007] The present invention is achieved in that:
[0008] In a first aspect, an embodiment of the present invention provides a method for preparing a super-hydrophobic coating, comprising: atomizing and drying a slurry obtained by mixing a fluorine-containing polymer with a ceramic powder to obtain a composite powder; and depositing the composite powder on a substrate using a thermal spraying technique to form a super-hydrophobic coating.
[0009] The volume ratio of the ceramic powder to the fluorine-containing polymer is 1:(0.25-0.75), the particle size of the ceramic powder is 0.5-5 μm, and the particle size of the fluorine-containing polymer is 50-250 nm.
[0010] In a second aspect, an embodiment of the present invention provides a super-hydrophobic coating, which is prepared by the preparation method described in the aforementioned embodiment.
[0011] In a third aspect, an embodiment of the present invention provides an application of the preparation method as described in the preceding embodiment in the preparation of a product having any one or more functions of super-hydrophobicity, wear resistance, corrosion resistance, anti-fouling and self-cleaning.
[0012] The present invention has the following beneficial effects:
[0013] (1) A uniform mixture of fluorinated polymer and ceramic powder is prepared by spray drying technology. This preparation method is simple and efficient, and it can ensure the hydrophobic properties of the super coating while giving it good wear resistance.
[0014] (2) By adjusting the particle size and mixing ratio of the fluorinated polymer and the ceramic powder, the prepared coating has both superhydrophobic properties and wear resistance and corrosion resistance;
[0015] (3) Through thermal spraying technology, the fluorinated polymer and ceramic composite coating is built up layer by layer, and a nanoscale transition layer is formed between the ceramic and the polymer, which greatly enhances the bonding strength of the coating. This coating structure gives the coating excellent wear resistance. After the outer layer is worn off, the inner layer can still maintain the hydrophobic function, so that the entire coating can effectively maintain the hydrophobic ability for a long time.
[0016] (4) When the coating prepared in the present application is used in friction conditions, the hard ceramic component in the coating has good mechanical properties and can effectively resist mechanical damage, especially friction and wear. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0018] Figure 1 This is a SEM image of the Al2O3 / PFA composite powder prepared in Example 2;
[0019] Figure 2(a) is a scanning electron microscope image of the Al2O3 / PFA composite coating prepared in Example 2, and (b) is a surface element distribution map of the Al2O3 / PFA composite coating prepared in Example 2;
[0020] Figure 3 The contact angle test results of the Al2O3 / PFA composite coating prepared in Example 2;
[0021] Figure 4 The friction performance test of the Al2O3 / PFA composite coating prepared in Example 2; (a) is a schematic diagram of the coating friction performance test process, and (b) is the coating contact angle test result during the coating friction performance test process;
[0022] Figure 5 The corrosion resistance test of the Al2O3 / PFA composite coating prepared in Example 2; (a) is a macroscopic image of the original morphology of the composite coating sample, (b) is the surface macroscopic morphology of the composite coating after a 60-day salt spray test, and (c) is a schematic diagram of the hydrophobic performance test of the composite coating after a 60-day salt spray test;
[0023] Figure 6 The antifouling performance test of the Al2O3 / PFA composite coating prepared in Example 2; (a1) to (e1) are schematic diagrams of soaking the Al2O3 / PFA composite coating in cola, orange juice, milk, sewage and soil particles for multiple times, respectively; (a2) to (e2) are the results of soaking the Al2O3 / PFA composite coating in cola, orange juice, milk, sewage and soil particles for multiple times, respectively;
[0024] Figure 7 This is the macroscopic morphology of the Al2O3 / PFA powder prepared in Example 3;
[0025] Figure 8 (a) is the appearance morphology of the Al2O3 / PFA coating sample prepared in Example 4; (b) is the macroscopic morphology of the Al2O3 / PFA coating sample prepared in Example 4 after scratching;
[0026] Fig. 9 (a) is the appearance morphology of the Al2O3 / PFA coating sample prepared in Example 5; (b) is the macroscopic morphology of the Al2O3 / PFA coating sample prepared in Example 5 after scratching;
[0027] Fig.10 (a) is a scanning electron microscope image of the Al2O3 / PFA composite coating prepared in Comparative Example 1; (b) is an element distribution diagram of the Al2O3 / PFA composite coating prepared in Comparative Example 1;
[0028] Fig.11The hydrophobic angle test results of the Al2O3 / PFA composite coating prepared in Comparative Example 1. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0030] Since fluoropolymers have a lower melting point than ceramic materials (about 340 ° C), it is difficult for those skilled in the art to conceive of depositing a composite coating of fluoropolymers and ceramic powders by high-temperature thermal spraying. The inventors of this application have found that ceramic powders with a specific particle size distribution and fluoropolymers with a specific particle size distribution are mixed in a specific proportion as raw materials, and the raw materials are prepared into composite powders with high sphericity and good fluidity by spray drying. The composite powder is then deposited by high-temperature thermal spraying technology to form a coating with super hydrophobicity, wear resistance and corrosion resistance. The preparation process provided in the embodiment of the present application also has the advantages of simple process, convenient operation, high efficiency, low cost and easy implementation, and has good repeatability, can be mass-produced, and can be widely used in the fields of surface corrosion protection, self-cleaning and anti-fouling.
[0031] On the one hand, an embodiment of the present invention provides a method for preparing a super-hydrophobic coating, comprising:
[0032] Atomizing and drying the slurry obtained by mixing the fluorine-containing polymer and the ceramic powder to obtain a composite powder;
[0033] Depositing the composite powder on a substrate using a thermal spraying technique to form a super-hydrophobic coating;
[0034] The volume ratio of the ceramic powder to the fluorine-containing polymer is 1:(0.25-0.75), the particle size of the ceramic powder is 0.5-5 μm, and the particle size of the fluorine-containing polymer is 50-250 nm.
[0035] The use of ceramic powders and / or fluorine-containing polymers with a particle size distribution larger than the above-set range will result in uneven distribution of the fluorine-containing polymer, a single coating structure and limited surface energy modification effect, ultimately affecting the superhydrophobic properties of the coating.
[0036] The low surface energy of the fluoropolymer itself makes the coating superhydrophobic. In some embodiments, the fluoropolymer includes any one or more of soluble polytetrafluoroethylene (PFA), polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF).
[0037] The high-hardness ceramic material makes the coating surface have good wear resistance. In some embodiments, the ceramic powder can be any one or more of oxide ceramics, carbide ceramics, nitride ceramics and metal-based tungsten carbide ceramics. The oxide ceramics can include any one or more of aluminum oxide, zirconium oxide, yttrium oxide, aluminum oxide-titanium oxide; the carbide ceramics can include any one or more of silicon carbide, boron carbide, and titanium carbide; the nitride ceramics can include any one or more of silicon nitride, aluminum nitride, and boron nitride; the metal-based tungsten carbide ceramics can include any one or more of tungsten carbide cobalt chromium, tungsten carbide nickel, and tungsten carbide Hastelloy.
[0038] In some embodiments, the ceramic powder includes alumina.
[0039] In some embodiments, the volume ratio of the ceramic powder to the fluorine-containing polymer (solid) may be any one of 1:0.25, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.75, or a range between any two of them.
[0040] In some embodiments, the particle size distribution of the ceramic powder may be any one of 0.5, 1, 2, 3, 4 and 5 μm or a range between any two thereof.
[0041] In some embodiments, the particle size distribution of the fluoropolymer can be any one of 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240 and 250 nm or a range between any two thereof.
[0042] In some embodiments, the fluorine-containing polymer mixed with the ceramic powder is a fluorine-containing polymer emulsion. Direct mechanical mixing of the ceramic powder and the solid powder of the fluorine-containing polymer easily leads to uneven distribution of the fluorine-containing polymer, resulting in uneven distribution of the fluorine-containing polymer in the coating, resulting in decreased hydrophobicity of the coating.
[0043] In some embodiments, in the fluorinated polymer emulsion, the mass fraction of the fluorinated polymer is 45% to 65%. The mass fraction can specifically be any one of 45%, 46%, 48%, 49%, 50%, 51%, 52%, 54%, 56%, 58%, 60%, 62%, 64% and 65%, or any two thereof.
[0044] The fluorine-containing polymer emulsion is obtained by mixing a fluorine-containing polymer with a surfactant. The preparation method provided in the embodiment of the present application has no special restrictions on the surfactant. In some embodiments, the surfactant includes: any one of sodium alkylbenzene sulfonate, polyethylene glycol fatty acid ester and fatty alcohol polyoxyethylene ether.
[0045] In some embodiments, the slurry further includes: any one or more of a dispersant, a binder and water.
[0046] In some embodiments, the preparation method includes: first mixing the fluorine-containing polymer, ceramic powder, water and dispersant in proportion, and then adding the binder.
[0047] In some embodiments, the dispersant includes polyacrylic acid (PAA), and the mass fraction of the dispersant in the slurry is 2% to 3%. The mass fraction can specifically be any one of 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9% and 3%, or a range between any two of the above.
[0048] In some embodiments, the binder includes polyvinyl alcohol (PVP), and the mass fraction of the binder in the slurry is 1.5% to 2%. The mass fraction can be any one of 1.5%, 1.6%, 1.7%, 1.8%, 1.9% and 2%, or a range between any two of the above.
[0049] The step of atomizing and drying the slurry obtained by mixing the fluorine-containing polymer and the ceramic powder can specifically be: injecting the slurry obtained by mixing the fluorine-containing polymer and the ceramic powder into a spray drying system, atomizing the slurry to form small droplets, and the atomized small droplets enter the drying chamber to exchange heat with the high-temperature air, and finally form a spherical powder product after drying and separation.
[0050] In some embodiments, the conditions for atomization drying include: an atomization pressure of 2 to 3 bar, an atomization air flow of 5 to 7 m 3 / h, the inlet temperature is 240~250℃, and the outlet temperature is 110~120℃. The inlet temperature and outlet temperature within the set range are conducive to improving the drying rate during spray drying, controlling the moisture content in the powder, the powder particle size, etc., below this set range will lead to incomplete drying of the material, and excessive moisture in the powder will affect its quality. Above this set range will cause the material to overheat or even denature. The inlet temperature can be any one of 240, 242, 244, 246, 248, 250℃ or a range between any two of them. The outlet temperature can specifically be any one of 110, 112, 114, 116, 118, 120℃ or a range between any two of them.
[0051] In some embodiments, before the atomization drying, the preparation method further includes preheating the granulation equipment, and when the inlet temperature reaches the set value of 240-250°C and the outlet temperature reaches 110-120°C, and the equipment runs stably, feeding at a speed of 35-40 rpm is started to prepare the powder.
[0052] In some embodiments, after atomization drying and before thermal spraying, the preparation method further comprises: pre-treating the substrate, wherein the pre-treatment comprises: at least one of rust removal, degreasing and sandblasting roughening.
[0053] In some embodiments, the sandblasting pressure used for the sandblasting is 0.3~0.4 MPa, and the workpiece is sandblasted at a distance of about 8~10 cm from the workpiece; the sandblasting particle composition is Al2O3 (46# corundum sand), and the roughness Ra of the substrate surface after sandblasting is 3~5 μm.
[0054] In some embodiments, the blasting pressure is any one of 0.3, 0.32, 0.34, 0.36, 0.38 and 0.4 MPa or a range between any two thereof.
[0055] In some embodiments, the parameters of the thermal spraying are: the spray gun power is 40~50 kW, the current is 450~650 A; the working gas flow rate is Ar: 30~45 splm, H2: 4~12 slpm, the powder feeding rate is 25~60 g / min; the spraying distance is 90~140 mm, the plasma gun moves horizontally, and the movement speed is 500~1000 mm / s. Relying on the characteristics of thermal spraying technology, by controlling the process parameters, the deposited coating retains the properties of the raw materials, and the thermal spraying process has a compacting effect on the coating, and the compacted deposited coating is dense. In addition, based on the extremely cold (10000~100000K / s) characteristics of thermal spraying, a nano-level transition layer can be formed at the interface between ceramics and fluoropolymers. Therefore, the coating has good bonding strength. The spraying parameters within the above-set range overcome the spraying technology problem of the low melting point of fluoropolymers, avoid or reduce the overburning carbonization and decomposition of PFA in the composite powder, and can achieve stable deposition in a high temperature environment, opening up a new path for the preparation of super-hydrophobic, wear-resistant and anti-corrosion coatings.
[0056] Specifically, the spray gun power can be any one of 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50kW or a range between any two of them. The current can be any one of 450, 460, 480, 500, 520, 540, 560, 580, 600, 620, 640, 650A or a range between any two of them. The working gas flow Ar can be any one of 30, 32, 34, 35, 36, 38, 40, 42, 44, 45splm or a range between any two of them. The working gas flow H2 can be any one of 4, 6, 8, 10, 12splm or a range between any two of them. The powder feeding rate can be any one of 25, 30, 35, 40, 45, 50, 55, 60 g / min or a range between any two of them. The spraying distance can be any one of 90, 100, 110, 120, 130, 140 mm or a range between any two thereof. The horizontal movement speed of the plasma gun can be any one of 500, 600, 700, 800, 900, 1000 mm / s or a range between any two thereof.
[0057] In some embodiments, the substrate is fabric, metal, glass, wood, ceramic, paper, plastic, or rubber.
[0058] On the other hand, an embodiment of the present invention provides a super-hydrophobic coating, which is prepared by the preparation method described in any of the aforementioned embodiments.
[0059] In addition, an embodiment of the present invention also provides the use of the preparation method as described in any of the foregoing embodiments in the preparation of a product having any one of the functions of superhydrophobicity, wear resistance, corrosion resistance, antifouling and self-cleaning, or integrating multiple functions.
[0060] In some embodiments, the products include: hydrophobic, wear-resistant and anti-corrosion coatings for pipes, valves, outer walls of ships and offshore platform components.
[0061] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0062] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0063] In the examples, the hydrophobic angle of the composite coating was measured by a contact angle meter (dataphys-OCA25) according to GB / T 24368-2009 standard.
[0064] In the embodiment, the friction performance test of the composite coating is carried out by weight and sandpaper according to the JB / T 7506-1994 standard. Sandpaper with a mesh of 1000 is selected, and a weight with a load of 100 g is placed on the surface of the composite coating sample and pushed back and forth for a distance of 10 cm. One back and forth push is regarded as a wear cycle, and the contact angle is measured after every 25 cycles.
[0065] In the embodiment, according to GB / T 10125-2021 standard, the composite coating sample was tested for 60 days in a cyclic salt spray tester (M2020030) under 35°C and 3.5 wt.% NaCl conditions, and the macroscopic morphology characteristics of the coating surface of the sample after the test were observed.
[0066] In the examples, the antifouling performance of the sample coating was tested according to GB / T 30159.1-2013 standard.
[0067] Example 1
[0068] This embodiment provides a method for preparing a super hydrophobic coating, which comprises the following steps:
[0069] (1) Let the average particle size be d 50 =1 μm Al2O3 powder (ZY-Al2O3-u001b, MCC New Materials) was mixed with PFA emulsion (DuPont, USA, 335D, PFA d50 particle size = 150nm) with a solid content of 60% and deionized water, wherein the volume ratio of Al2O3 powder to PFA solid in PFA emulsion was 1:0.25, and then polyacrylic acid PAA dispersant (final concentration of 3wt%) was added, and stirred evenly with a magnetic stirrer for spray drying to prepare powder for use. Spray drying technology, before spray drying, the granulation equipment needs to be preheated, and after the inlet temperature reaches 250 ℃ and the equipment runs stably, start feeding at a speed of 35 rpm; the feeding pressure is 2.0 Pa, and during this process, the spray drying slurry is stirred at a speed of 450 rpm to avoid its sedimentation. The prepared powder is collected at the outlet of the spray drying equipment.
[0070] (2) Degrease, remove rust and roughen the surface with sandblasting on the stainless steel substrate, then clean it with alcohol for later use.
[0071] (3) The spray gun power is 45kW, the current is 620A; the working gas flow rate is Ar: 40 splm, H2: 10 slpm, the powder feeding rate is 25 g / min; the spraying distance is 110 mm, the plasma gun moves horizontally, and the movement speed is 800 mm / s. The Al2O3 / PFA composite coating was prepared using these spraying parameters.
[0072] Example 2
[0073] This embodiment provides a method for preparing a hydrophobic coating, which is substantially the same as that of Embodiment 1, except that in step (1), the volume ratio of Al2O3 powder to PFA solid in PFA emulsion is 1:0.5.
[0074] The scanning electron microscope images of the Al2O3 / PFA agglomerated powder prepared in Example 2 and the energy spectrum element point analysis of different powder particles are as follows: Figure 1 And as shown in Table 1.
[0075] Table 1 Spectral element analysis of different powder particles
[0076]
[0077] Depend on Figure 1 It can be seen that the powder obtained by spray drying has a high sphericity, and the four elements Al, O, F, and C in the agglomerated powder are evenly distributed as a whole, which ensures the stable powder feeding during plasma spraying, the stability of the coating preparation process, and the uniformity of the coating composition and performance.
[0078] The scanning electron microscope image and element distribution diagram of the Al2O3 / PFA composite coating of Example 2 are shown in FIG. Figure 2 As shown in (a) and (b).
[0079] Depend on Figure 2 It can be seen that the composite coating is composed of a loose porous structure constructed by spherical and filamentary substances, and the filamentary structure is evenly distributed between the spherical structures. It was characterized by energy dispersive spectrometer and found that the composite coating is composed of characteristic elements C, F, Al and O, which are relatively evenly distributed on the coating surface. These filamentary structures are unique to PFA, and the spherical structure material is Al2O3. Based on the above analysis, it can be seen that the Al2O3 / PFA composite coating was prepared by thermal spraying technology using the Al2O3 / PFA agglomerated powder obtained by spray drying.
[0080] Figure 3 The contact angle test results of the Al2O3 / PFA composite coating prepared in Example 2 show that the contact angle of the Al2O3 / PFA composite coating reaches above 150°, showing an excellent super-hydrophobic state.
[0081] Figure 4 The water contact angle variation trend diagram of the composite coating in Example 2 after different wear cycles shows that the water contact angle generally shows a gradually decreasing trend with the increase of the number of wear times; however, after 100 wear cycles, i.e., the wear distance is 2000 cm, the contact angle of the coating is still greater than 150°, indicating that the coating still has excellent superhydrophobic properties after 100 wear cycles, and the coating has good wear resistance.
[0082] Figure 5 This is the macroscopic morphology of the coating after the corrosion resistance test of the composite coating in Example 2. The super-hydrophobic Al2O3 / PFA composite coating was subjected to a salt spray resistance test for 60 days at a temperature of 35°C and a concentration of 3.5wt.% NaCl. Figure 5 (a) is a macroscopic image of the original morphology of the composite coating sample. The coating has uniform color and no defects such as color difference spots and peeling. Figure 5 (b) shows the surface macroscopic morphology of the super-hydrophobic Al2O3 / PFA composite coating after 60 days of salt spray test. It was found that water droplets were suspended on the surface of the coating and failed to penetrate the coating, and there was no obvious pitting corrosion at any position of the coating. Figure 5 (c) is a schematic diagram of the hydrophobic performance test of the composite coating after 60 days of salt spray test. Water droplets roll down on the surface of the coating, indicating that the composite coating still maintains excellent hydrophobic performance after 60 days of salt spray test, and has good corrosion resistance.
[0083] Figure 6 The antifouling performance test process and results of the composite coating in Example 2. In order to prove the antifouling performance of the prepared composite coating in various application environments, liquids with different surface tensions were tested. Cola, orange juice, milk, sewage and soil particles commonly seen in life were selected as polluted liquids, and then the super-hydrophobic Al2O3 / PFA composite coating was repeatedly immersed in the polluted liquid and lifted up after 15 seconds. After multiple immersions, Figure 6 The coating surface is still very clean without any residual pollutant liquid. The results show that the Al2O3 / PFA composite coating has good antifouling performance.
[0084] Example 3
[0085] This embodiment provides a method for preparing a hydrophobic coating, which is substantially the same as that of Embodiment 1, except that in step (1), the volume ratio of Al2O3 powder to PFA solid in PFA emulsion is 1:1.
[0086] In order to further improve the hydrophobic angle of the coating, the present embodiment increases the PFA solid solution content during the spray drying process so that the volume ratio of Al2O3 powder to PFA solid is 1:1. The Al2O3 / PFA powder finally prepared is as follows Figure 7 As shown, it can be found that the powders are all agglomerated together and have no fluidity at all. This indicates that when the PFA content is high during the spray drying process, Al2O3 / PFA powder suitable for thermal spraying cannot be prepared, that is, Al2O3 / PFA coating cannot be prepared.
[0087] Example 4
[0088] This embodiment provides a method for preparing a hydrophobic coating, which is substantially the same as that of Embodiment 2, except that in step (3), the thermal spraying process parameters are adjusted as follows: the spray gun power is 35 kW, the current is 550 A; the working gas flow rate is Ar: 40 splm, H2: 6 slpm, the powder feeding rate is 25 g / min; the spraying distance is 110 mm, the plasma gun moves in the horizontal direction, and the movement speed is 800 mm / s. The coating is prepared using the above spraying parameters.
[0089] In order to further improve the hydrophobicity of the coating and reduce the amount of PFA carbonization during the spraying process, the spraying power was reduced. When the spraying power was 35 kW, the macroscopic morphology of the prepared Al2O3 / PFA coating sample was as follows: Figure 8 The coating surface is loose, because the Al2O3 ceramic powder has a melting point of nearly 2050℃, and the power of 35kW cannot make it melt well, and finally the Al2O3 / PFA coating with uniform and complete surface cannot be prepared.
[0090] Example 5
[0091] This embodiment provides a method for preparing a hydrophobic coating, which is substantially the same as that of Embodiment 2, except that in step (3), the thermal spraying process parameters are adjusted as follows: the spray gun power is 50 kW, the current is 650 A; the working gas flow rate is Ar: 45 splm, H2: 12 slpm, the powder feeding rate is 25 g / min; the spraying distance is 110 mm, and the plasma gun moves in the horizontal direction at a movement speed of 800 mm / s.
[0092] Example 5: The spraying power was increased to 50 kW. The macroscopic morphology of the coating sample finally prepared was as follows: Fig. 9 As shown in (a), the coating surface presents obvious wrinkles and irregular shapes, resulting in an uneven coating surface, and the coating is prone to warping and peeling (such as Fig. 9 This is because the spraying temperature increases with the increase of spraying power, and the substrate temperature is also high. When the powder particles are deposited on the substrate surface with a higher temperature, the PFA material with a lower melting point warps, making the final prepared coating uneven and flat, affecting the hydrophobicity and mechanical properties of the coating.
[0093] Comparative Example 1
[0094] This comparative example provides a method for preparing a hydrophobic coating, which comprises the following steps:
[0095] (1) Al2O3 powder with a particle size distribution of 5 to 25 μm and PFA powder with a particle size distribution of 5 to 30 μm are mixed by mechanical mixing at a volume ratio of 1:0.75 for spraying.
[0096] (2) Degrease and remove rust from the substrate, then roughen the surface of the stainless steel substrate by sandblasting, and then clean it with alcohol for later use.
[0097] (3) The spray gun power is 45 kW, the current is 620 A; the working gas flow rate is Ar: 45 splm, H2: 8 slpm, the powder feeding rate is 25 g / min; the spraying distance is 110 mm, the plasma gun moves horizontally, and the movement speed is 800 mm / s. The Al2O3 / PFA coating was prepared using the above spraying parameters.
[0098] The Al2O3 / PFA composite coating prepared by mechanical mixing method (Comparative Example 1) was tested and found to have only a certain degree of hydrophobicity, with a hydrophobic angle of 130° (<150°) and not reaching the super-hydrophobic state. At the same time, the surface and cross-sectional morphology of the coating also showed the uneven distribution of PFA in the coating, which was also the reason for the uneven hydrophobicity of the coating.
[0099] Fig.10 This is the surface element distribution diagram of the Al2O3 / PFA composite coating prepared by mechanically mixing Al2O3 and PFA powders. It can be seen that the distribution of PFA in the coating is very uneven, which affects the hydrophobic performance of the coating.
[0100] Fig.11 It is the test result of hydrophobic angle, including the hydrophobic angle of pure alumina coating, Al2O3 / PFA coating prepared by mechanical mixing method (Comparative Example 1), and Al2O3 / PFA coating prepared by spray granulation method (Example 2). It can be seen that the hydrophobic angle of alumina coating is only 38°, which has no hydrophobic effect; the hydrophobic angle of mechanically mixed Al2O3 / PFA coating in Comparative Example 1 is 130°, which has a certain hydrophobic effect, and the hydrophobic angle of spray granulated Al2O3 / PFA coating is 152°, which achieves super hydrophobic effect.
[0101] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a super hydrophobic coating, characterized in that, It includes: Atomizing and drying the slurry obtained by mixing the fluorine-containing polymer and the ceramic powder to obtain a composite powder; Depositing the composite powder on a substrate using a thermal spraying technique to form a super-hydrophobic coating; Wherein, the volume ratio of the ceramic powder to the fluorine-containing polymer is 1:(0.25-0.75), the particle size of the ceramic powder is 0.5-5 μm, and the particle size of the fluorine-containing polymer is 50-250 nm; The fluorine-containing polymer mixed with the ceramic powder is a fluorine-containing polymer emulsion, and the mass fraction of the fluorine-containing polymer in the fluorine-containing polymer emulsion is 45% to 65%.
2. The preparation method according to claim 1, characterized in that: The fluorine-containing polymer includes: any one or more of soluble polytetrafluoroethylene and polyvinylidene fluoride; The ceramic powder includes any one or more of oxide ceramic powder, carbide ceramic powder, nitride ceramic powder and tungsten carbide-based metal ceramic powder.
3. The preparation method according to any one of claims 1 to 2, characterized in that The slurry further includes: any one or more of a dispersant, a binder and water.
4. The preparation method according to claim 3, characterized in that: The dispersant includes polyacrylic acid, and the mass fraction of the dispersant in the slurry is 2% to 3%.
5. The preparation method according to any one of claims 1 to 2, characterized in that The conditions of the atomization drying include: the atomization pressure is 2-3 bar, the atomization air flow is 5-7 m 3 / h, the inlet temperature is 240~250℃, and the outlet temperature is 110~120℃.
6. The preparation method according to any one of claims 1 to 2, characterized in that The parameters of the thermal spraying are: the spray gun power is 40~50 kW, the current is 450~650 A; the working gas flow rate is Ar: 30~45 splm, H2: 4~12 slpm, the powder feeding rate is: 25~60 g / min; the spraying distance is: 90~140 mm, the plasma gun moves in the horizontal direction, and the movement speed is: 500~1000 mm / s.
7. The preparation method according to any one of claims 1 to 2, characterized in that The substrate is fabric, metal, glass, wood, ceramic, paper, plastic or rubber.
8. A super hydrophobic coating, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 7.
9. Application of the preparation method according to any one of claims 1 to 7 in preparing a product having any one of the functions of super-hydrophobicity, wear resistance, corrosion resistance, antifouling and self-cleaning or integrating multiple functions.
Citation Information
Patent Citations
Non-stick coating, preparation method of non-stick coating, cooker and cooking equipment
CN109957750A
Superhydrophobic antibacterial cationic fluorine-containing polymer nanocoating
CN110885592A
Hydrophobic anti-corrosion coating material and preparation method thereof
CN112080716A